Effects of light-curing time on the cytotoxicity of a restorative resin composite applied to an immortalized odontoblast-cell line - Costa, CAD; Hebling, J.; Hanks, C. T. (Operative Dentistry Inc, 2003)
This in vitro study evaluated the cytotoxic effects of a restorative resin composite applied to an immortalized odontoblast-cell line (MDPC-23). Seventy-two round resin discs (2-mm thick and 4 mm in diameter) were light-cured for 20 or 40 seconds and rinsed, or not, with PBS and culture medium. The resin discs were divided into four experimental groups: Group 1: Z-100/20 seconds; Group 2: Z-100/20 seconds/rinsed; Group 3: Z100/40 seconds; Group 4: Z-100/40 seconds/rinsed. Circular filter paper was used as a control material (Group 5). The round resin discs and filter papers were placed in the bottom of wells of four 24-well dishes (18 wells for each experimental and control group). MDPC-23 cells (30,000 cells/cm(2)) were plated in the wells and allowed to incubate for 72 hours. The zone of inhibition around the resin discs was measured under inverted light microscopy; the MTT assay was carried out for mitochondrial respiration and cell morphology was measured under SEM. The scores obtained from inhibition zone and MTT assay were analyzed with the Kruskal-Wallis followed by Dunnett tests. In Groups 1, 2, 3 and 4, the thickness of the inhibition zone was 1,593 +/- 12.82 mum, 403 +/- 15.49 mum, 1,516 +/- 9.81 mum and 313 +/- 13.56 mum, respectively. There was statistically significant difference among the experimental and control groups at the 0.05 level of significance. The MTT assay demonstrated that the resin discs of the experimental groups 1, 2, 3 and 4 reduced the cell metabolism by 83%, 40.1%, 75.5% and 24.5%. Only between the Groups 2 and 4 was there no statistically significant difference for mitochondrial respiration. Close to the resin discs, the MDPC-23 cells exhibited rounded shapes, with only a few cellular processes keeping the cells attached to the substrate or, even disruption of plasma membrane. Adjacent to the inhibition zone, the cultured cells exhibited multiple fine cellular processes on the cytoplasmic membrane organized in epithelioid nodules, similar to the morphology observed to the control group. Based on the results, the authors may conclude that the Z-100 resin composite light cured for 20 seconds was more cytopathic to MDPC-23 cells than Z-100 light cured for 40 seconds. The cytotoxic effects of the resin discs decreased after rinsing them with PBS and culture medium. This was confirmed by MTT assay and upon evaluation of the inhibition zone, which was narrower following rinsing of the resin discs.